IMPLEMENTATION OF ACADEMIC SUPERVISION BY THE PRINCIPLE OF PUBLIC JUNIOR HIGH SCHOOLS IN PROBOLINGGO CITY - Zainuddin; Munirul Abidin; Abdul Bashith (Al-Fikru : Jurnal Pendidikan Dan Sains, 2023)
Academic supervision is one of a school principal's main duties and responsibilities. This study aims to describe the academic supervision practices of principals in public junior high schools based on teachers' perceptions. This study was conducted in Probolinggo City East Java Province, by distributing a questionnaire to 109 teachers in three selected SMPNs. The questionnaire had been validated using the expert judgment technique. The data collected from the questionnaire were analyzed quantitatively. The findings show that the public junior high school principals supervised the teachers regarding their teaching-related responsibilities. The prominent supervision practice exercised by the principals was motivating teachers to take advantage of information technology in teaching. The weakest one performed by the principals was related to helping teachers in developing the syllabus required by the current national curriculum. Thus, some school principals’ academic supervision practices still need improvement..Keywords: academic supervision, principalship